In situ template-free synthesis of a novel 3D p–n heteroarchitecture Ag3PO4/Ta3N5 photocatalyst with high activity and stability under visible radiation1. Issue 77 (22nd August 2015) - Wang, Wen; Fang, Hua-Bin; Zheng, Yan-Zhen; Che, Yanke; Tao, Xia; Chen, Jian-Feng
<x xml:space="preserve">Abstract</x> This 3D heteroarchitecture Ag3PO4/Ta3N5 photocatalyst shows double visible-light response characteristics and sufficient hetero-interfaces between Ag3PO4 and Ta3N5.